Effect of strain rate on tensile properties of polyurethane/(multiwalled carbon nanotube) nanocomposite. Issue 3 (19th November 2014) - Moghim, Mohammad Hadi; Zebarjad, Seyed Mojtaba
Abstract : In this research, polyurethane (PU)/(carbon nanotube) (CNT) samples, with two different contents of multiwalled carbon nanotubes (MWCNTs; i.e., 0.5 and 1.0 wt%) were fabricated through a solution casting method. To investigate the effect of strain rate on tensile properties, tensile tests were done on standard samples at constant temperature and different strain rates (2 × 10 −5 to 2 × 10 −2 s −1 ). Eyring's model was performed to clarify the role of both strain rate and CNTs content on activation volume and activation enthalpy of PU. To elucidate the role of strain rate and CNTs content on fracture behavior of PU, fracture surfaces of some samples were also investigated by scanning electron microscopy. The results of tensile tests show the intense effect of strain rate on tensile properties of PU/MWCNTs nanocomposites. Also, it was proved that the dependency of tensile properties of PU nanocomposites on strain rate decreases as CNTs content increases. The microscopic observations of the samples also demonstrate that increasing the strain rate changes the behavior of the fracture surface to less a ductile fracture, and increasing CNTs content causes much surface roughness. Finally, by investigation of the activation enthalpies, it is confirmed that much higher enthalpy is needed to fracture the samples with increased MWCNTs content, as the activation enthalpy changes from 45 for neat PU to 131 kJ/mol for PU/(1% MWCNTs) samples. J. VINYL ADDIT. TECHNOL., 22:356–361, 2016. © 2014 Society of Plastics Engineers